Spinal Surgery During COVID-19 Pandemic in Saudi Arabia - Faisal Konbaz; Taif Alqahtani; Nada Alharthi; Mohammad Baraja; Nazish Masud; Sami Aleissa; Fahad Alhelal; Majed Abalkhail (Journal of Spine Practice)
Introduction: The COVID-19 pandemic has challenged the healthcare system’s capacities around the world. Due to the alarming situation, medical activities have been restricted to allocate resources to treat COVID-19-infected patients. However, medical emergencies still need urgent medical intervention. Considering the lack of reliable data regarding spinal surgeries during the COVID-19 pandemic, the present study sought to analyze the pattern of spinal surgeries in KSA.